Delayed Reconstruction by Total Calcaneal Allograft following Calcanectomy: Is It an Option? - Benjamin Degeorge; Louis Dagneaux; David Forget; Florent Gaillard; François Canovas (Case Reports in Orthopedics)
Many options are available in literature for the management of delayed reconstruction following calcanectomy. In cases of low-grade tumor lesions, conservative surgery can be considered. We describe a case of delayed reconstruction by calcaneal allograft after calcanectomy for low-grade chondrosarcoma. At 12-month follow-up, the patient had no pain; MSTS score and AOFAS score were satisfactory. Subtalar nonunion was observed with no secondary displacement or graft necrosis. The aim of conservative treatment for this patient was to restore normal gait with plantigrade locomotion and function of the Achilles tendon. Calcaneal reconstruction by total allograft is an alternative approach following calcanectomy for calcaneal tumors. We also discussed other options of calcaneal reconstruction.